Comparative Analysis Of The Efficiency; Asset Quality And Financial Stability Between National Private Commercial Banks (BUSN) And Local Development Bank (BPD) In Indonesia - Laode Arman Saipura (Tanjungpura International Journal on Dynamics Economics, Social Sciences and Agribusiness, 2022)
This research aims to compare efficiency, quality of assets and financial stability between Nasional Private Commercial Bank (BUSN) and Regional development Banks (BPD). Efficiency variables are formulated with the ratio of operating costs compared to the operating income (BOPO), the quality of the asset is made in the ratio of non-performing Loan (NPL), namely the comparison of problematic financing with total Financing, and financial stability that is redefined with Return On Asset (ROA) is a comparison of the profit generated by the bank with the total assets owned by the bank. The method in this research is the quantitative method of usingdescriptive test, Classic Assumption test and Mann Whitney test. Based on the descriptive results and Mann Whitney test, the efficienc, the quality of the asset and financial stability of the Nasional Private Commercial Banks (BUSN) is better when compared to the Regional development Banks (BPD).